2017
DOI: 10.3390/met7120552
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Study on the Excitation of Guided Waves in Rectangular Plates Using Multiple Point Sources

Abstract: Ultrasonic guided waves are widely used to inspect and monitor the structural integrity of plates and plate-like structures, such as ship hulls and large storage-tank floors. Recently, ultrasonic guided waves have also been used to remove ice and fouling from ship hulls, wind-turbine blades and aeroplane wings. In these applications, the strength of the sound source must be high for scanning a large area, or to break the bond between ice, fouling and plate substrate. More than one transducer may be used to ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…A few studies have been conducted to selectively generate the Lamb wave mode in a finite-width plate. In one study, a selective excitation method using multiple point sources was numerically studied, and it was found that the performance of the proposed method varied with the number of point sources [ 13 ]. In another study, a mode selection method using phased array was investigated [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have been conducted to selectively generate the Lamb wave mode in a finite-width plate. In one study, a selective excitation method using multiple point sources was numerically studied, and it was found that the performance of the proposed method varied with the number of point sources [ 13 ]. In another study, a mode selection method using phased array was investigated [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The schematic of this setup is illustrated in Figure 6. This type of FEM synthesis of guided wave signals in pipes was developed in previous studies [37,[46][47][48][49][50]. The generated models have also been validated by confirming the accuracy of the received signals from both the device [50], and 3D laser vibrometer [46,47].…”
Section: Finite Element Modelmentioning
confidence: 69%
“…Recent work by Surojo et al [29] discussed the influence of the water flow and depth/location on welding performance using mechanical testing. Another possibility for extension of this work could involve marine vessels, e.g., the hull structure of a ship [30][31][32][33][34][35][36]. The subject is no longer on the material specimen scale, but the use of a down-scaled hull prototype or weld could be used to represent parts of the ship structure, such as the frame and side hull.…”
Section: Discussion Of the Experimentsmentioning
confidence: 99%